If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(-9-2x)=-21
We move all terms to the left:
3(-9-2x)-(-21)=0
We add all the numbers together, and all the variables
3(-2x-9)-(-21)=0
We add all the numbers together, and all the variables
3(-2x-9)+21=0
We multiply parentheses
-6x-27+21=0
We add all the numbers together, and all the variables
-6x-6=0
We move all terms containing x to the left, all other terms to the right
-6x=6
x=6/-6
x=-1
| 36=w/2+29 | | 3c+15=3(c×5) | | 2(3+10m)=5(1+4m) | | 32÷n=4n= | | 6+2(a+(3+a))=80 | | 9d+10=91 | | w=2w-22 | | 2/5(3x-2)=3x-4 | | 2+3(-4x-2)=x-5(8x+6) | | 7(q-78)=98 | | 11c+70=20c+61 | | 2n^2+4n-4=-6 | | (x+23)=(5x-9) | | 11z-34=6z+1 | | x/7/6=-2 | | 2y-24=y+5 | | x/(7/6)=-2 | | d-72/5=4 | | -x-x=-(x-1) | | y-2*3=-30-2y | | 8b=6b-22 | | 2u+47=9u+33 | | 60=12x0.5x=1 | | 125m-100m+38,600=40,000-175m | | -2(4g-5)+6(2g+1)=8 | | 9a-43=137 | | x^2+10x-24=32 | | 4(-4x+3)+3=3(-6x+6)-2x | | y-3y+18=-4y-2 | | 25(3x-2)=3x-4 | | 8(4x+4)=2 | | x(-7)=5 |